Vivo até a morte: ensaio sobre a identidade na velhice - Akkari, Paula Farias (2023)
This study sought to undersrtand the process of identity formation in the elderly in the light of the identity-metamorphosis-emancipation syntagm porposed by Ciampa. The starting point was na exploration of his theory. A discussion was held on the foundations of the old age – characterized by a decrease in interection with the world –, which encompassed a panorama of material conditions that underpn it, with a particular emphasis on the Covid-19 pandemic. Data collection was carried out through the narrative of life stories, approached hermeneutically to elucidate meanings, characters, contradictions and emancipatory fragments. Once the results are amalgamated, the conclusion pointed to the incessantly metamorphic character of selfcreation